2018
DOI: 10.1089/acm.2017.0262
|View full text |Cite
|
Sign up to set email alerts
|

“It's Better in a Group Anyway”: Patient Experiences of Group and Individual Acupuncture

Abstract: Patients in both arms valued their acupuncture experience. Participants described both positive and negative aspects of the group setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
2
14
1
Order By: Relevance
“…Participants who might have had an initial preference for individual treatment reliably initiated and continued treatment in the group setting. In qualitative interviews with participants in both study arms, 77 we identified both positive (social interaction) and negative (privacy concerns, mixed-gender groups) elements, but none of these ultimately affected initiation and continuation of treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Participants who might have had an initial preference for individual treatment reliably initiated and continued treatment in the group setting. In qualitative interviews with participants in both study arms, 77 we identified both positive (social interaction) and negative (privacy concerns, mixed-gender groups) elements, but none of these ultimately affected initiation and continuation of treatment.…”
Section: Discussionmentioning
confidence: 92%
“…For example, Tofthagen et al [13] reported significant improvement in cancer-related pain and numbness for patients undergoing group AP; however, they used a retrospective study design and had no comparison group. Similarly, in a qualitative study, Chuang et al [12] reported that patient experiences in group AP were on par with individual AP for pain relief and improvement in QoL; however, their findings were limited 6…”
Section: Discussionmentioning
confidence: 99%
“…Group (or community) AP is an emerging cost-effective method of treating patients. Although the practice can vary, group AP is performed in a group setting, typically with reclining chairs dispersed around a large room, and one practitioner treating up to six people per session [11,12]. Despite its growing popularity, there is relatively little evidence to demonstrate the effectiveness of AP performed in a group setting.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary data have helped to clarify acceptability of community/group acupuncture; potential barriers such as language, working status, child care duties, functional disability and opioid analgesic use were not found to be deterrents to treatment. 32,33 Randomization to group acupuncture did not affect treatment initiation or retention. 34…”
Section: Introductionmentioning
confidence: 96%
“…Qualitative evaluation of participants receiving acupuncture in both individual and group settings is described in a separate paper. 33…”
Section: Introductionmentioning
confidence: 99%